Pengaruh Spiritual Well-Being terhadap Pendampingan Pembelajaran Daring pada Ayah Singgle Parent - Sarkowi, Sarkowi (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
The impact of COVID-19 has also hit educational institutions with a policy of changing learning from an offline system to an online system. This condition requires parents to provide online learning assistance for their children. This research was conducted to analyze and measure the effect of spiritual well-being on the effect of online learning assistance on the resilience of single parent fathers after the  covid 19 pandemic. A total of 150 single parent fathers were involved by filling out an online survey related to the Spiritual Well Being Index for single parent fathers and Child Learning Assistance. The results stated that there was an influence of "spiritual well-being" on online learning assistance with an effect of 48.0%. Thus, "Spiritual well-being" is one that must be prioritized because it can be used as a variable that plays a very important role in the success of accompanying parents to their children in learning